Cost-effective data replication mechanism modelling for cloud storage. (12th January 2023) - Zaman, Khalid; Hussain, Altaf; Imran, Muhammad; Sohail, Muhammad
Replication increases data availability and reduces access latency in cloud storage. Solutions prioritise system performance over replica production and storage costs. Under a pay-as-you-go model, cloud users incur rising fees for replica storage and consistency management. Before expanding node copies, we outline a dynamic replication technique. The suggested technique concentrates resources for effective distribution across all nodes. The cost-effectiveness of the proposed model is determined using threshold values; the proposed system reduced cloud replicas, reducing costs. Azure's 6 static solution has three nodes. The adaptive data replication management system reduces copies from three to two, saving memory and reducing price from 6 to 4. MATLAB and other programming languages are used. Azure is compared to Date Replication and Reproducer (DRR). The proposed solution is cheaper than Azure with three replicates.